Helicobacter pylori is undetectable in intraductal papillary mucinous neoplasm - BAYSAL, Birol; Ince, ALİ TÜZÜN; İNCE, ALİ TÜZÜN; SÜMBÜL, BİLGE; Gucin, ZÜHAL; GÜCİN, ZÜHAL; Malya, FATMA ÜMİT; MALYA, FATMA ÜMİT; TOZLU, Mukaddes; Senturk, HAKAN; ŞENTÜRK, HAKAN; BAĞCI, PELİN; et al. (My University, 2016)
Background: About half of the world population is infected with Helicobacter pylori (H. pylori), a bacterium associated with gastric cancer and considered to be a risk factor for pancreatic ductal adenocarcinoma. Whether the bacterium is associated with intraductal papillary mucinous neoplasm, believed to be a precursor of pancreatic ductal adenocarcinoma, is unknown. The aim of this study was to investigate the presence of H. pylori DNA in tissue sections of intraductal papillary mucinous neoplasm.